2010
DOI: 10.1158/0008-5472.can-09-3470
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 Drives a Positive Feedback Loop to Reinforce the Wnt/β-Catenin/TCF Signaling Axis

Abstract: Activation of the Wnt signaling pathway occurs frequently in human cancers, but an understanding of the targets and regulation of this important pathway remains incomplete. In this study, we report that phospholipase D (PLD), a cell survival mediator that is upregulated in cancer, is an important target of the Wnt signaling pathway that functions in a positive feedback loop to reinforce pathway output. PLD1 expression and activity was enhanced by treatment with Wnt3a and glycogen synthase kinase-3 inhibitors, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…We recently identified transcriptional activation of PLD by Wnt3a, and the second messenger PA produced by PLD further induced activation of the Wnt/b-catenin-signaling target genes via promotion of the b-catenin/TCF-4 transcription complex (4,5). We found that the expression levels of PLD and b-catenin are significantly correlated in colorectal cancer tissues, which supports the presence of a strong link between the Wnt/b-catenin pathway and PLD in vivo.…”
Section: Phospholipase D Activates Wnt/b-catenin Signaling Via a Posisupporting
confidence: 69%
See 3 more Smart Citations
“…We recently identified transcriptional activation of PLD by Wnt3a, and the second messenger PA produced by PLD further induced activation of the Wnt/b-catenin-signaling target genes via promotion of the b-catenin/TCF-4 transcription complex (4,5). We found that the expression levels of PLD and b-catenin are significantly correlated in colorectal cancer tissues, which supports the presence of a strong link between the Wnt/b-catenin pathway and PLD in vivo.…”
Section: Phospholipase D Activates Wnt/b-catenin Signaling Via a Posisupporting
confidence: 69%
“…4,[13][14][15][16][17][18]. Considering the role for PLD in tumor progression, PLD inhibitors have emerged as potential anticancer drugs.…”
Section: Phospholipase D and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The Wnt pathway is critical in tissue development and is frequently mutated in many cancers (Kikuchi, 2003). Recent studies have shown that PLD1 is a transcriptional product of Wnt activation and participates in a feed-forward mechanism in which PLD activity is required for transcription of a number of Wnt-responsive genes (Kang et al, 2010). Although EMT gene expression was not measured in the study, PLD may potentially regulate EMT and loss of adhesion through Wnt.…”
Section: F Activating Invasion and Metastasismentioning
confidence: 92%